2014
DOI: 10.1242/jeb.106294
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory strategy may shape immune investment inDrosophila melanogaster

Abstract: As temperatures change, insects alter the amount of melanin in their cuticle to improve thermoregulation. However, melanin is also central to insect immunity, suggesting that thermoregulatory strategy may indirectly impact immune defense by altering the abundance of melanin pathway components (a hypothesis we refer to as thermoregulatory-dependent immune investment). This may be the case in the cricket Allonemobius socius, where warm environments (both seasonal and geographical) produced crickets with lighter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 28 publications
1
24
0
5
Order By: Relevance
“…2013; Kutch et al. 2014). Moreover, environmental cooling or warming may affect the likelihood of transmission or impact of disease at both organism and population levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2013; Kutch et al. 2014). Moreover, environmental cooling or warming may affect the likelihood of transmission or impact of disease at both organism and population levels.…”
Section: Introductionmentioning
confidence: 99%
“…While changes in the thermal environment may trigger direct physiological and behavioral responses at the organism level, it may also indirectly trigger such responses through alternative pathways. In insects, for example, a greater resistance to a pathogenic challenge can be reached via changes in cuticular melanization, which enhances the immune investment pleiotropically (Fedorka et al 2013;Kutch et al 2014). Moreover, environmental cooling or warming may affect the likelihood of transmission or impact of disease at both organism and population levels.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in both butterflies and Anopheles stephensi demonstrated that phenoloxidase activity was higher at cool temperatures and becomes less efficient at warmer temperatures (Suwanchaichinda and Paskewitz, 1998; Murdock et al, 2012b). The production of melanin is also essential for other physiological processes such as cold acclimization in insects (Crill et al, 1996; Kutch et al, 2014) the formation of the hard protective layer around eggs, and wound healing (Lai et al, 2009). Our data also reveal that c-type lectin, reported to participate in activation of the melanization cascade (Yu and Kanost, 2000; Christensen et al, 2005) was also up-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Melanic forms of H. axyridis are thought to have a fitness advantage at low temperatures because their dark colour may enable them to absorb heat and increase body temperature more rapidly than non-melanic forms [5,51,54]. Besides, previous studies have shown that a darker cuticle can reduce rates of water loss [55][56][57], and increase immune function [58][59].…”
Section: Relationship Between Elytral Colour and Ambient Temperaturementioning
confidence: 99%